Voluntary organizations and local governance - Mangada, Ladylyn L. (1998)
This study examined the receptivity of voluntary organizations to local governance. Drawing inspiration from perceptions that individuals/groups from poor, non-urban setting are reluctant to face new challenges in governance, the paper explored the issue in favor of the 4th to 6th class municipalities, in particular, those located in Easter/Western Samar and Leyte provinces. More specifically, the study aimed to examine the receptivity of voluntary organizations to local governance in terms of: a) their response to new challenges of governance, b) comparative advantages and disadvantages, and c) nature of interaction with the bureaucracy.